An investigation into the role of methylation in mammalian X-chromosome inactivation - Ian., S; Simpson T. Ian (1999)
﻿ X-chromosome inactivation achieves dosage compensation of X-linked genes between male (XY) and female (XX) mammals. This process involves the down-regulation of most, but not all genes on one of the two X-chromosomes in the nucleus of each female somatic cell. The mechanism of X-inactivation has yet to be elucidated in full, but is known to involve the noncoding transcript of theXist gene, DNA methylation, histone hypo-acetylation and the condensation of higher order chromatin. Recent studies have established mechanisms linking methylation to repressive chromatin structures through methyl-binding proteins and histone deacetylase complexes. In order to better understand the role of methylation in X-inactivation, the promoters of the human Pyruvate dehydrogenase El a (PDHA1) and the human and murine Norrie disease protein (NDP/Ndp) genes were subjected to direct methylation sequencing, allowing the definition of methylation profiles at nucleotide resolution. The promoter of the PDHA1 gene was found to be hyper-methylated on the inactive X-chromosome and hypo-methylated on the active X-chromosome in agreement with studies at the promoters of other X-linked housekeeping genes. Methylation at the promoters of the NDP/Ndp genes was extensively investigated in a range of primary tissues and cell lines. The Ndp promoter was found to be methylated on both active and inactive X-chromosomes, but hypo-methylated in the proximal promoter exclusively in tissues that expressed the Ndp gene. The NDP promoter was found to be unmethylated on the active X-chromosome and hyper-methylated across the proximal promoter on the inactive X-chromosome in expressing cell lines and human retinal tissues. The novel promoter sequences of the human and murine SMCX/Smcx genes were isolated for comparative analysis and to provide a future resource for studying methylation at the promoters of genes which escape the X-inactivation process. Promoter sequences of the PDHA1, NDPI Ndp and SMCX/Smcx genes were screened for putative transcription factor binding sites and for conserved CpG-dinucleotide content. Promoter-reporter gene constructs for these genes were transfected into mammalian cells establishing that the sequences studied were functional promoters. Artificial methylation of these constructs was shown to repress their promoter activities.